Using an Alternating Treatment Design in a Co-taught Classroom to Measure Student On-task Behavior - Keeley, Randa G. (Journal of the American Academy of Special Education Professionals, 2018)
The purpose of this study was to determine if student on-task behavior varied when a) the One Teach/One Assist co-teaching model was applied or b) when the Team Teaching model was applied using an alternating treatment design for four students in a co-taught Algebra I classroom. Results show that participants experienced increased on-task behavior and an overall decrease in behavior variation when the One Teach/One Assist or Team Teach co-teaching model was implemented. These findings indicate that in a co-taught classroom, whether the One Teach/One Assist or Team Teaching model is implemented it will yield increased on-task behavior of students as compared to not implementing a co-teaching model.